Cross and crescent : responding to the challenge of Islam - Chapman, Colin, 1938- (Downers Grove, Ill. : IVP Books, 2007)
"Is the Muslim my neighbor? For increasing numbers of Christians, the answer is yes. The crescent, emblem of the Islamic faith recognized throughout the world, is gaining prominence in the West, bringing with it a collision of worldviews." "When the cross meets the crescent, what ought to happen? In the newly revised classic Cross and Crescent, Colin Chapman brings sensitivity and humanity to the question that too often incites hostility and suspicion. He introduces Islam in its historical context, its theological assumptions and, most important, its common practice in the West. In this comprehensive, gracious introduction to Islam, you will meet the Muslims in your community and learn how to love these neighbors as yourself."--BOOK JACKET.
Relating to our Muslim neighbors. Meeting face to face -- Appreciating Islamic culture -- Examining our attitudes -- Understanding Islam. What is Islam? -- Basic Muslim beliefs and practices -- Muslims at prayer -- The life of Muhammad -- The Qur'an -- Tradition (hadith and sunna) -- Law (Shari'a) and theology (kalam) -- Sufism -- Folk Islam or popular Islam -- The spread and development of Islam -- Branches and movements within Islam -- Issues facing Muslims today -- Women in Islam -- "Islamic terrorism" -- Entering into discussion and dialogue. Questions and objections concerning Christian practice -- Social and political issues -- Questions and objections concerning Christian beliefs -- Guidelines in discussion with Muslims -- A deeper look at the main Muslim objections -- Learning from the controversies of the past -- Exploring dialogue -- Facing fundamental issues. Theological questions -- The Islamic view of Jesus -- The Qur'anic view of Christians -- Crucial differences : the parting of the ways -- Thinking Biblically about Islam -- Counting the cost of conversion -- Facing the political challenge of Islam -- Bearing witness to Jesus. Natural openings in everyday life -- Using the Bible -- Starting from the Qur'an -- Explaining Christian beliefs about Jesus -- Some issues facing Christians today.
Includes bibliographical references (p. [377]-389) and index.
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Islam -- Essence, genius, nature